Allergic Contact Dermatitis of the Scalp: Analysis of Allergen Profiles - Kasumagic-Halilovic, Emina; Ovcina- Kurtovic, Nermina; Suljagic, Omar; Gujic, Enis (British Journal of Healthcare and Medical Research, 2026)
Background: Allergic scalp contact dermatitis (ASCD) is a delayed type of hypersensitivity from contact with a specific allergen to which the patients has developed a specific sensitivity. The aim of the study was to evaluate the results of patch testing with standard series of contact allergen in patients suspected to have ASCD. Methods: 112 cases of scalp contact dermatitis were included in the study. Test substances were applied on the upper part of the patient’s back, on clinically uninvolved and untreated skin. The patch test was removed and reaction were evaluated after 48 h and 72 h. The grading of negative (-) to positive (+ to ++++) patch test was done in accordance with the International Contact Dermatitis Research Group. Results: Among the 112 cases, 83 patients were female (74.1 %) and 29 were male (25.9 %). The age of participants spanned 17 to 72 years. The commonest age group affected was 41-50 years. The most common positive reactions were recorded to nickel sulphate 22 (26.2%), cobalt chloride 18 (21.4%), fragrance mix 16 (19%), balsam of Peru 14 (16.7%), carba mix 8 (9.5%) and paraphenylenediamine 5 (5.9%). Females were more likely to show a positive response to two or more allergens. Scalp itching or burning were reported as the most common symptom. Conclusions: Scalp ACD predominantly affects middle-aged women. Our results suggest that nickel sulphate and cobalt are the predominant allergens responsible for the induction of ASCD. These findings are crucial in the treatment, long term management, and education of patients with ASCD.